Utilizing Superoxide Dismutase Mimetics to Enhance Radiation Therapy Response While Protecting Normal Tissues - Mapuskar, Kranti A. (Semin Radiat Oncol, 2019)
Symptomatic normal tissue injury is a common side effect following definitive therapeutic radiation and chemotherapy treatment for a variety of malignancies. These cancer therapy related toxicities may occur acutely during treatment resulting in reduced or missed therapy agent administration or after the completion of therapy resulting in significant chronic morbidities that significantly diminish patient quality of life. Radiation and chemotherapy induce the formation of reactive oxygen species (ROS) both in normal tissues and tumor cells. One type of ROS common to both chemotherapy and radiation therapy is the formation of superoxide (O(2)(•−)). Fortunately, due to metabolic differences between cancer and normal cell metabolism, as well as improved targeting techniques, ROS generation following radiation and chemotherapy is generally greater in cancer cells compared to normal tissues. However, the levels of ROS generated in normal tissues are capable of inducing significant toxicity. Thus, several groups are focusing on metabolism-based approaches to mitigate normal tissue effects occurring both during and following cancer therapy. This review will summarize the most current pre-clinical and clinical data available demonstrating the efficacy of small molecule, superoxide dismutase mimetics in minimizing radiation and chemotherapy-induced normal tissue injury, resulting in enhanced patient outcomes.